A potential sudden stop of energy imports from Russia: Effects on energy security and economic output in Germany and the EU - Eva M. Berger; Sylwia Bialek; Niklas Garnadt; Veronika Grimm; Lars Other; Leonard Salzmann; Monika Schnitzer; Achim Truger; Volker Wieland (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2022)
[Introduction] The Russian war of aggression against Ukraine since 24 February 2022 has intensified the discussion of Europe's reliance on energy imports from Russia. A ban on Russian imports of oil, natural gas and coal has already been imposed by the United States, while the United Kingdom plans to cease imports of oil and coal from Russia by the end of 2022. The European Commission has announced on 5 April 2022 to ban coal imports from Russia (Europäische Kommission, 2022a). It has been wrestling with the idea of an oil and gas embargo against Russia. At the same time, Russia may decide to stop its energy exports to countries that are imposing sanctions. The German Federal Government is currently opposing an energy embargo against Russia (BMWK, 2022a). However, the Federal Ministry for Economic Affairs and Climate Action (BMWK) is working on a strategy to reduce energy imports from Russia (BMWK, 2022b, 2022c). The urgency to reduce dependency on Russian gas seemed to have increased particularly after the Russian president announced Russia would accept only the Russian currency Ruble for energy exports - even though the issue seems to have been solved by energy importers opening accounts at the Gazprom bank. On 30 March 2022 the BMWK has declared early warning, i.e., the first of three crises levels according to the emergency plan for gas (BMWK, 2022d), which is based on the EU regulation 2017/1938 concerning measures to safeguard the security of gas supply (BMWK, 2022d). The crisis level of early warning primarily serves at improving information flows and cooperation between the relevant authorities; currently, no market intervention is undertaken. In this paper we first give an overview of the German and European reliance on energy imports from Russia with a focus on gas imports (Section II) and we discuss price effects (Section II.1), alternative suppliers of natural gas (Section II.2), and the potential for saving and replacing natural gas (Section II.3). In Section III, we provide an overview of estimates of the consequences on the economic outlook if the conflict intensifies. Section IV concludes.
Keywords: 330; Energieversorgung; Gasversorgung; Russisch; Energiepolitik; Wirkungsanalyse; Schätzung; Deutschland